THE RELATIONSHIP OF KNOWLEDGE AND SELF-MANAGEMENT TO THE STRESS LEVEL OF UNDERGOING A DIABETES MELLITUS DIET - Putri Maharani; Selamat Parmin; Alvian Harisandy (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Diabetes mellitus (DM) is a chronic metabolic disorder with increasing prevalence every year, which causes several severe consequences. An important aspect of diabetes care is dietary management; however, adherence to diet often causes stress in patients. Self-management knowledge and competence contribute significantly to the patient's ability to reduce stress and increase the success of the diet regimen. This study aims to determine the correlation between knowledge and self-management with stress levels in diabetes mellitus patients who adhere to the diet at Bhayangkara Mohamad Hasan Hospital Palembang in 2025. This study used a quantitative methodology with a cross-sectional design. A sample of 94 respondents was selected using a random sampling method, using a questionnaire to assess knowledge, self-management, and stress levels of patients. The study was conducted in June–July 2025 for 3 weeks at the Internal Medicine Outpatient Clinic of Bhayangkara Mohamad Hasan Hospital Palembang. Data were analyzed using the chi-square test. The results showed that most respondents demonstrated high knowledge (87.2%), good self-management (58.5%), and low stress levels (88.3%). The chi-square test showed a significant relationship between knowledge and stress levels (p=0.000) and between self-management and stress levels (p=0.047). This study showed that increased patient awareness of diabetes diet and better self-management methods correlated with decreased stress levels when adhering to the diet. This study underscores the need for education and support in self-management for diabetes patients to improve quality of life and reduce the risk of stress.